Threats to Political Information Environment and Democracy: Polish Politicians’ Perceptions - Stępińska, Agnieszka (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2024)
The current political information environment (PIE) is in flux undergoing a series of well documented changes. These changes may affect the conditions for a healthy democracy being oftentimes associated with a growing number of uninformed, selectively informed, or even misinformed citizens. While each of these specific changes has received a lot of individual attention, less is known about the perceptions held by political elites towards the threats and opportunities associated with the PIE. This qualitative study examines the main concerns, challenges, and threats that representatives of political elites perceive with regards to the current political information environment. The analyses are based on a series of in-depth interviews conducted with politicians in Poland. The investigation revealed some shared perceptions among politicians across ideological orientations on challenges related to the current developments in the media, as well as differences in perceptions on their causes and potential solutions. Środowisko informacji politycznej podlega wielu zmianom, które mogą mieć wpływ na demokrację. W szczególności zmiany te mogą prowadzić do zwiększenia liczby niepoinformowanych, posiadających jednostronny obraz rzeczywistości społecznej lub wprowadzonych w błąd obywateli. O ile każdemu z tych problemów poświęca się obecnie dużo uwagi, o tyle niewiele jest badań ukazujących, jak te wyzwania (ale także szanse) postrzegają aktorzy polityczni. Celem artykułu jest prezentacja wyników badania z wykorzystaniem metody indywidualnego wywiadu pogłębionego przeprowadzonego z udziałem polskich polityków. Wyniki badania ukazały podobieństwa w zakresie tego, co politycy z różnych partii postrzegają jako zagrożenia. Główne różnice ujawniły się w zakresie przypisywanych tym zagrożeniom przyczyn oraz sugerowanych rozwiązań.
Zagrożenia dla środowiska informacji politycznej z perspektywy polskich polityków
Keywords: political information; threats; democracy; perception; political actor; Poland; informacja polityczna; zagrożenia; demokracja; percepcja; aktor polityczny; Polska